2021
DOI: 10.1186/s13006-021-00386-0
|View full text |Cite
|
Sign up to set email alerts
|

Achieving global targets on breastfeeding in Thailand: gap analysis and solutions

Abstract: Background Global advocates for breastfeeding were evident since the International Code of Marketing of Breast-Milk Substitutes (BMS Code) was adopted in 1981 and fostered by subsequent relevant World Health Assembly resolutions, using a framework that promotes, supports and protects breastfeeding. Global partners provided comprehensive support for countries to achieve breastfeeding targets while progress was closely monitored. This review identifies breastfeeding policy and implementation gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…In this study, respondents with high education and digital literacy, when faced with breastfeeding problems, tended to seek advice and solutions from social media (Internet and Facebook pages) rather than through health personnel and lactation clinics. This implies that current counselling services for lactating mothers are not convenient or responsive [42,43]. Hence, further study is needed to evaluate and review existing health services and guidelines related to breastfeeding support, as well as the compliance with the BFHI recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, respondents with high education and digital literacy, when faced with breastfeeding problems, tended to seek advice and solutions from social media (Internet and Facebook pages) rather than through health personnel and lactation clinics. This implies that current counselling services for lactating mothers are not convenient or responsive [42,43]. Hence, further study is needed to evaluate and review existing health services and guidelines related to breastfeeding support, as well as the compliance with the BFHI recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that poor-latching and insufficient breastmilk supplies are common reasons for EBF discontinuation. 23,25,40,42 Despite health professionals' critical roles, existing breastfeeding support for Thai mothers, particularly during the early post-partum period, is still inadequate and needs significant reform; 43,44 only 7.7% of infants in Thailand were put to the mother's breast after birth and only 34% were initially breastfed within an hour after birth in 2019. 6 Inadequate breastfeeding follow-up is a result of a shortage of lactation counselors and other competing responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 6-month exclusive breastfeeding rate in Thailand has changed over time. A series of national surveys reported that the rate was 14.5% in 2005 and increased to 23.1% in 2016, which was the highest; however, it sharply decreased to 14.0% in 2019 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%